2017
DOI: 10.4049/jimmunol.1700175
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TRAF6 Mediates TLR/IL-1R Signaling–Induced Nontranscriptional Priming of the NLRP3 Inflammasome

Abstract: NLRP3 inflammasome activiation requires two sequential signals. The priming signal 1 from TLRs or cytokine receptors induces the transcription of NLRP3 and IL-1β, and concomitantly promotes transcription-independent activation of caspase-1. The activating signal 2 can be provided by microbial products or danger signals. In this study we found that TRAF6 is necessary for the nontranscriptional priming of NLRP3 inflammasome by TLR/IL-1R derived signals. Deficiency of TRAF6 specifically inhibited TLR/IL-1R primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 23 publications
2
90
0
Order By: Relevance
“…Furthermore, we observed the inhibition of RIPK2, which is a potent activator of NF-κB and inducer of apoptosis. In addition, we observed the downregulation of TRAF6 gene expression, which may inhibit caspase-1 cleavage, pyroptosis, and pre-synthesized IL-18 secretion (Xing et al, 2017). Upregulation of IL-6 and TXNIP genes upon CRID3 exposure may help in reducing oxidative stress and inflammatory response.…”
Section: Cytokine Release Inhibitory Drug 3 Inhibits Inflammasome Regmentioning
confidence: 77%
“…Furthermore, we observed the inhibition of RIPK2, which is a potent activator of NF-κB and inducer of apoptosis. In addition, we observed the downregulation of TRAF6 gene expression, which may inhibit caspase-1 cleavage, pyroptosis, and pre-synthesized IL-18 secretion (Xing et al, 2017). Upregulation of IL-6 and TXNIP genes upon CRID3 exposure may help in reducing oxidative stress and inflammatory response.…”
Section: Cytokine Release Inhibitory Drug 3 Inhibits Inflammasome Regmentioning
confidence: 77%
“…TRAF6 has been shown to mediate IL-1R signalling-induced non-transcriptional priming of the NLRP3 inflammasome. 37 Recently, it has been shown that circulating levels of cell death markers (cK18, K18) were significantly lower in patients with cirrhosis with previous AD. This may reflect a dominant cell death (IL-1α) response in individuals without prior AD, but an NLRP3 response (IL-1β) if there has been prior AD.…”
Section: Discussionmentioning
confidence: 99%
“…29 Importantly, inhibiting the inflammasome restores normal hematopoiesis 29 and protects against the development of cardiovascular disease in TET2-deficient mice. 30 TRAF6 is involved in TLR-mediated priming of the NLRP3 inflammasome in BM-derived macrophages, 31 suggesting that TLR signaling via TRAF6 is also linked to inflammasome activation in MDS.…”
Section: Functional Evidence Of Innate Immune Signaling Dysregulationmentioning
confidence: 99%